Relation between osteocalcin and the energy metabolism in obesity - Nikolić, Stanislava; Ćurić, Nikola; Ilinčić, Branislava; Stošić, Zoran; Tomić-Naglić, Dragana; Benc, Damir (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Numerous findings have indicated the potential relation between the osteocalcin, the traditional parameter of bone turnover and the regulation of energy metabolism. The aim of this study was to identify the relationship between osteocalcin and calculated indexes, which evaluate insulin sensitivity, insulin resistance and/or secretory capacity of the pancreas, in non-diabetic, obese subjects. Methods. The study included 57 (11 men and 46 women) euglycemic, obese patients (the body mass index – BMI : 41.03 ± 6.61 kg/m²) and 48 healthy individuals, age and sex matched (BMI : 23.15 ± 2.04 kg/m²). Plasma glucose and the insulin levels during the two-hour oral glucose tolerance test (OGTT) were determined in order to calculate the Homeostatic Model Assessment (HOMA) indexes (HOMA-IR, HOMA-B%), EISI (estimated insulin sensitivity index), EFP (estimated first phase) and ESP (estimated second phase). Osteocalcin was measured by using the Electro-chemiluminescence (ECLIA) methodology. Results. Statistically lower osteocalcin was found in the obese subjects (24.72 ± 9.80 vs 33.31 ± 10.89 ng/mL; p
Keywords: obesity; insulin resistance; osteocalcin; pancreas; body mass index